1997
DOI: 10.1097/00005768-199705000-00037
|View full text |Cite
|
Sign up to set email alerts
|

ACSM Position Stand: The Female Athlete Triad

Abstract: The Female Athlete Triad is a syndrome occurring in physically active girls and women. Its interrelated components are disordered eating, amenorrhea, and osteoporosis. Pressure placed on young women to achieve or maintain unrealistically low body weight underlies development of the Triad. Adolescents and women training in sports in which low body weight is emphasized for athletic activity or appearance are at greatest risk. Girls and women with one component of the Triad should be screened for the others. Alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
177
0
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(198 citation statements)
references
References 94 publications
2
177
0
3
Order By: Relevance
“…We, therefore, constructed a pathogenetic model of stress fracture on the basis of studies in the adult literature and the observations of experienced clinicians. The risk factors deemed most important in our model included BMI, dietary intake of calcium and vitamin D, and heredity and were identified, a priori, as covariates to be measured in the study.Even before the American College of Sports Medicine coined the term "female athlete triad" in 1992 to describe the interrelatedness of disordered eating, amenorrhea, and osteoporosis in young female athletes, 17,18 another area of significant interest in women's skeletal health has been menstrual irregularity (MI). 19,20 Studies have inconsistently shown MI to be a risk factor for stress fracture in active adult women, 21-26 but information on menstrual history was not available from the large epidemiologic cohort that we analyzed previously.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We, therefore, constructed a pathogenetic model of stress fracture on the basis of studies in the adult literature and the observations of experienced clinicians. The risk factors deemed most important in our model included BMI, dietary intake of calcium and vitamin D, and heredity and were identified, a priori, as covariates to be measured in the study.Even before the American College of Sports Medicine coined the term "female athlete triad" in 1992 to describe the interrelatedness of disordered eating, amenorrhea, and osteoporosis in young female athletes, 17,18 another area of significant interest in women's skeletal health has been menstrual irregularity (MI). 19,20 Studies have inconsistently shown MI to be a risk factor for stress fracture in active adult women, 21-26 but information on menstrual history was not available from the large epidemiologic cohort that we analyzed previously.…”
mentioning
confidence: 99%
“…Even before the American College of Sports Medicine coined the term "female athlete triad" in 1992 to describe the interrelatedness of disordered eating, amenorrhea, and osteoporosis in young female athletes, 17,18 another area of significant interest in women's skeletal health has been menstrual irregularity (MI). 19,20 Studies have inconsistently shown MI to be a risk factor for stress fracture in active adult women, [21][22][23][24][25][26] but information on menstrual history was not available from the large epidemiologic cohort that we analyzed previously.…”
mentioning
confidence: 99%
“…[13][14][15] This constellation of disordered eating, amenorrhea, and osteoporosis has come to be known as the "female athlete triad," a term coined by the American College of Sports Medicine in 1993. 16,17 To begin to assess which stress fractures may be markers of compromised bone health, one must understand the epidemiology and causes of these injuries. Although stress fractures cause considerable impairment, 2 unfortunately little is known about the prevalence of or risk factors for stress fractures among young women.…”
mentioning
confidence: 99%
“…It is often accompanied with nutrition and menstrual cycle dysfunctions thus constituting a syndrome often called »Female Sports Triad« (12)(13)(14). Functional hypo thalamic amenorrhea (HPA) is a condition charac terized by the absence of menstrual cycle due to suppression of hypothalamic-pituitary-ovarian axis, without the presence of morphological or organic defects (5).…”
Section: Discussionmentioning
confidence: 99%